Exploring the use of control packets in LoRa medium access: a scalability analysis - Fernandes, Rui (2021)
LoRa technology has been attesting itself as one of the most prominent and widely adopted low power wide area technologies. Highly compatible with Internet of Things (IoT) applications and urban environments, this technology enables large range communications although with small bandwidths and duty cycle restrictions. In this work, we propose a distinct way of dealing with the Medium Access Control (MAC) in LoRa, through the use of control packets to enhance the technology performance in urban city scenarios, where a large number of nodes is expected. The proposed protocol is asynchronous and takes into account the energy expenditure. We compare this scheme with the standard (LoRaWAN) by considering different network densities and packet sizes, and through different LoRa collision models. Performance results, such as network throughput and fairness index, show that, depending on the ratio between data and control packet lengths, it is possible to greatly improve the bit rate and overall network performance, even if increasing the duty-cycle restriction time due to the addition of overhead.